2004
DOI: 10.1158/1078-0432.ccr-03-0103
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Clinical Significance of Heparan Sulfate Proteoglycans in Ovarian Cancer

Abstract: Purpose: Heparan sulfate proteoglycans have been implicated in cancer cell growth, invasion, metastasis, and angiogenesis. This study was designed to compare their expression in normal ovary and ovarian tumors and then to examine their prognostic significance in ovarian cancer.Experimental Design: The expression of syndecan-1, -2, -3, and -4, glypican-1, and perlecan was assessed by immunohistochemistry in 147 biopsies that included normal ovary and benign, borderline, and malignant ovarian tumors. Clinical da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
112
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(123 citation statements)
references
References 45 publications
9
112
0
2
Order By: Relevance
“…CD138 is normally expressed in the epithelial cells and some mesenchymal cells such as plasma cells and immature B lymphocytes. However, it has been demonstrated that CD138 is expressed by the stromal cells in the some neoplastic and non-neoplastic odontogenic lesions (ameloblastoma, KCOT and DC), and ovarian cancers, as well as plasma cells (24,33). It has also been stated that the expression of CD138 is associated with poor prognosis (24, 33).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CD138 is normally expressed in the epithelial cells and some mesenchymal cells such as plasma cells and immature B lymphocytes. However, it has been demonstrated that CD138 is expressed by the stromal cells in the some neoplastic and non-neoplastic odontogenic lesions (ameloblastoma, KCOT and DC), and ovarian cancers, as well as plasma cells (24,33). It has also been stated that the expression of CD138 is associated with poor prognosis (24, 33).…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been demonstrated that CD138 is expressed by the stromal cells in the some neoplastic and non-neoplastic odontogenic lesions (ameloblastoma, KCOT and DC), and ovarian cancers, as well as plasma cells (24,33). It has also been stated that the expression of CD138 is associated with poor prognosis (24,33). CD138 (syndecan 1) shifting from epithelium to stroma was reported in invasive non-odontogenic solid tumors including breast, prostate, lung, and colon cancers (21).…”
Section: Some Authors Suggested That Loss Of E-cadherin Expression Inmentioning
confidence: 99%
“…A correlation between CD138 expression and carcinogenesis has been investigated in various organs. Increased expression of CD138 has been reported in endometrial and ovarian carcinomas (6,7). By contrast, decreased expression of CD138 has been reported to correlate with tumor invasion and progression of cervical cancer (8-10).…”
Section: Discussionmentioning
confidence: 99%
“…HB-EGF contains a heparan sulfate binding motif that enables its binding to heparan sulfate proteoglycans (HSPG) in the coelomic epithelium. An analysis of HSPG expression in normal OSE compared to that derived from tumors evinced normal patterns for all cell surface PGs except syndecan-1 (SDC1), which was highly expressed in tumor cells but absent from normal epithelium [80]. In addition, only SDC1 and glypican-1 were associated with poor prognoses in univariate analysis.…”
Section: Growth Factors In Emt and Angiogenesismentioning
confidence: 96%